Highly efficient AgBr/h-MoO3 with charge separation tuning for photocatalytic degradation of trimethoprim: Mechanism insight and toxicity assessment - Cai, Zhengqing; Yougui Song; Xibiao Jin; Chong-Chen Wang; Ji, Haodong; Liu, Wen; Xianbo Sun (Science of The Total Environment, 2021)
A highly solar active AgBr/h-MoO3 composite was constructed by a facile precipitation method, and the charge separation tuning was achieved by photoreduction of AgBr. The photoreduced Ag0 on AgBr/h-MoO3 acted as charge transfer bridge to form Z-scheme heterostructure, while the high degree of Ag reduction converted the material into type-II heterostructure. The synthesized optimal material promoted charge separation and visible light activity due to the incorporation of highly solar active AgBr, which showed ca. 2 times activity on trimethoprim (TMP) degradation than h-MoO3. The contribution of reactive species on TMP degradation followed the order of O2− > 1O2 > h+, which agree well with the proposed charge separation mechanism. The photocatalytic degradation mechanism of TMP was proposed based on the radical quenching, intermediate analysis and DFT calculation. The toxicity analysis based on QSAR calculation showed that part of the degradation intermediates are more toxic than TMP, thus sufficient mineralization are required to eliminate the potential risks of treated water. Moreover, the material showed high stability and activity after four reusing cycles, and it is applicable to treat contaminants in various water matrix. This work is expected to provide new insight into the charge separation tuning mechanism for the AgX based heterojunction, and rational design of highly efficient photocatalysts for organic contaminants degradation by solar irradiation.
Keywords: AgBr/h-MoO; Charge separation tuning; Photocatalysis; Toxicity; Trimethoprim